Visualizing Human Protein‐Protein Interactions and Subcellular Localizations on Cell Images Through CellMap. Issue 1 (9th March 2020) - Dallago, Christian; Goldberg, Tatyana; Andrade‐Navarro, Miguel Angel; Alanis‐Lobato, Gregorio; Rost, Burkhard
Abstract: Visualizing protein data remains a challenging and stimulating task. Useful and intuitive visualization tools may help advance biomolecular and medical research; unintuitive tools may bar important breakthroughs. This protocol describes two use cases for the CellMap (http://cellmap.protein.properties ) web tool. The tool allows researchers to visualize human protein‐protein interaction data constrained by protein subcellular localizations. In the simplest form, proteins are visualized on cell images that also show protein‐protein interactions (PPIs) through lines (edges) connecting the proteins across the compartments. At a glance, this simultaneously highlights spatial constraints that proteins are subject to in their physical environment and visualizes PPIs against these localizations. Visualizing two realities helps in decluttering the protein interaction visualization from "hairball" phenomena that arise when single proteins or groups thereof interact with hundreds of partners. © 2019 The Authors. Basic Protocol 1 : Visualizing proteins and their interactions on cell images Basic Protocol 2 : Displaying all interaction partners for a protein